2012
DOI: 10.1111/j.1399-6576.2012.02648.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐administration sequence of target‐controlled propofol and remifentanil influences the onset of rocuronium. A double‐blind, randomized trial

Abstract: The onset time of rocuronium is prolonged significantly by early administration of remifentanil during target-controlled infusion of propofol and remifentanil, and it may be due to the decreased CO caused by remifentanil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…The discrepancy in the results among studies perhaps can be explained in terms of the critical role of timing in the priming technique; a priming interval of 3 minutes accelerates onset, but a 2-minute interval does not [12]. In the present study, remifentanil may have delayed rocuronium circulation time to the relevant neuromuscular cleft by decreasing cardiac output [13]; thus, the effect of the priming dose may have been attenuated.…”
Section: Discussioncontrasting
confidence: 56%
“…The discrepancy in the results among studies perhaps can be explained in terms of the critical role of timing in the priming technique; a priming interval of 3 minutes accelerates onset, but a 2-minute interval does not [12]. In the present study, remifentanil may have delayed rocuronium circulation time to the relevant neuromuscular cleft by decreasing cardiac output [13]; thus, the effect of the priming dose may have been attenuated.…”
Section: Discussioncontrasting
confidence: 56%
“…Propofol causes vasodilatation and myocardial depression . For remifentanil, a previous study documented that its prior administration delays onset of rocuronium during TIVA most likely due to a decrease of cardiac output . In this study, we did not measure cardiac output, but the haemodynamic response before induction of anaesthesia and before injection of rocuronium suggests similar haemodynamic conditions in both groups consisting of healthy patients (ASA I–II).…”
Section: Discussionmentioning
confidence: 71%
“…A series of studies showed that propofol administration was associated with cardiovascular protective effects, including decreased blood pressure, systemic vascular resistance, and antioxidant properties. Moreover, propofol inhibited production of proinflammatory cytokines and inducible nitric oxide synthase, as well as neutrophil chemotaxis, attachment, and migration, phagocytosis, and reactive oxygen species production, and can scavenge free radicals, decrease lipid peroxidation, and inhibit platelet aggregation [43,44]. In this study, we addressed the missing link between propofol treatment and increasing cholesterol efflux by providing evidence that propofol administration was positively associated with expression of ABCA1, ABCG1, and SR-B1, possibly by propofol induced-up-regulation of PPARγ/LXRα expression.…”
Section: Discussionmentioning
confidence: 99%